2021
DOI: 10.1016/j.nefro.2020.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Fracaso renal agudo en pacientes hospitalizados por COVID-19

Abstract: Antecedentes y objetivo: En diciembre de 2019 surgió en Wuhan, China, la COVID-19 causada por SARS-CoV-2, declarada pandemia global por la OMS en marzo de 2020. Es una infección respiratoria con complicaciones a nivel cardiaco, hematológico, digestivo, neurológico y renal. El fracaso renal agudo (FRA) en pacientes hospitalizados por COVID-19 se presenta en el 0,5-25% y es un factor de mal pronóstico. Los mecanismos de afectación renal no están completamente aclarados. Presentamos la evolución clínica de pacien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 19 publications
1
10
0
8
Order By: Relevance
“…The mechanisms include ischemic injury due to fluid loss and heart failure, cytokine release syndrome, exposure to nephrotoxins, rhabdomyolysis, microcirculatory thrombi, hypercoagulability, direct podocyte and epithelial lesion, RAAS activation and renal vasoconstriction. 18 , 33 , 34 Consistent with this, in our cohort AKI was more frequent in patients with higher disease severity, higher inflammatory markers and also in patients exposed to nephrotoxins, namely contrast, nonsteroidal anti-inflammatory drugs, vancomycin and aminoglycosides.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The mechanisms include ischemic injury due to fluid loss and heart failure, cytokine release syndrome, exposure to nephrotoxins, rhabdomyolysis, microcirculatory thrombi, hypercoagulability, direct podocyte and epithelial lesion, RAAS activation and renal vasoconstriction. 18 , 33 , 34 Consistent with this, in our cohort AKI was more frequent in patients with higher disease severity, higher inflammatory markers and also in patients exposed to nephrotoxins, namely contrast, nonsteroidal anti-inflammatory drugs, vancomycin and aminoglycosides.…”
Section: Discussionsupporting
confidence: 88%
“…In COVID-19 patients, kidney impairment appears to be multifactorial resulting from systemic inflammatory response to volume loss, sepsis, local disruption in renin angiotensin aldosterone system (RAAS) homeostasis, rhabdomyolysis, and it is also suggested that the virus might have direct cytopathic effects. 13 , 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
“…The incidence of AKI in our patients was 19%, in agreement with the incidence reported in previous studies that ranges from 18% to 30.6% [ 28 , 29 ]. Various studies have described AKI in COVID-19 patients and the factors associated with this outcome [ 30 , 31 ]. This phenomenon is probably underestimated in our population.…”
Section: Discussionmentioning
confidence: 99%
“…Queremos transmitir en nombre de todos los autores el agradecimiento por mostrar interés en nuestra publicación como se refleja en su carta al director 1 , 2 .…”
unclassified